Non-invasive Differentiation of Endometrial Adenocarcinoma from Benign Lesions in the Uterus by Utilization of Amide Proton Transfer-Weighted MRI. - Li, Yuan; Lin, Cheng-Yu; Qi, Ya-Fei; Wang, Xiao-Qi; Chen, Bo; Zhou, Hai-Long; Ren, Jing; Yang, Jun-Jun; Xiang, Yang; He, Yong-Lan; Xue, Hua-Dan; Jin, Zheng-Yu (Molecular Imaging & Biology, 2021)
Purpose: To evaluate the utility of three-dimensional (3D) amide proton transfer-weighted (APTw) imaging for differentiation of endometrial adenocarcinoma and uterine benign lesions.Procedures: This prospective study enrolled 22 normal volunteers and 113 patients with suspicious uterine lesions, including endometrial adenocarcinoma, leiomyoma, and adenomyosis. Pelvic APTw MRI was performed on a 3-T MRI scanner with default APTw parameters. Two radiologists blindly evaluated uterine lesion APTw image quality by a 3-point Likert scale and independently measured APTw values on images with excellent to good image quality. Inter-reader agreement was evaluated. The Mann-Whitney U test with Bonferroni correction was used to compare the differences among different types of uterine lesions. A receiver operating characteristic analysis was performed.Results: A total of 111 lesions (33 endometrial adenocarcinoma, 26 leiomyoma, and 52 adenomyosis lesions) from 99 patients revealing a majority of good quality with excellent inter-reader agreement were included for the image quality evaluation. APTw values of endometrial adenocarcinoma were 2.9 ± 0.1 %, significantly higher than those of leiomyoma (1.9 ± 0.1 %), adenomyosis (2.2 ± 0.1 %), and normal uterine myometrium (1.9 ± 0.1 %) (all p < 0.0001). The area under the receiver operating characteristic curve for differentiating endometrial adenocarcinoma from leiomyoma, adenomyosis, and myometrium was 0.87, 0.85, and 0.91, respectively. Feasible threshold APTw values of each group were determined as 2.4 %, 2.7 %, and 2.4 % with a sensitivity of 83.3 %, 76.7 %, and 83.3 % and a specificity of 83.3 %, 81.6 %, and 86.4 %, respectively.Conclusions: Malignant endometrial adenocarcinoma had significantly higher APTw values than leiomyoma, adenomyosis, and normal uterine myometrium. Our study adds to the growing body of validation on 3D APTw imaging and uterine lesions.